2007
DOI: 10.3168/jds.s0022-0302(07)72630-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Varying Doses of Supplemental Conjugated Linoleic Acid on Production and Energetic Variables During the Transition Period

Abstract: Supplementing a high dose of dietary conjugated linoleic acid (CLA) inhibits milk fat synthesis in dairy cows immediately postpartum. During negative net energy balance (EBAL), it appears that moderate CLA-induced milk fat depression causes a positive response in milk yield; however, as milk fat depression becomes more severe, the milk yield response diminishes. Multiparous Holstein cows (n = 31) were randomly assigned to 1 of 3 treatments beginning 9 +/- 6 d before expected calving and ceased at 40 d in milk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
96
3
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(120 citation statements)
references
References 31 publications
20
96
3
1
Order By: Relevance
“…This is in contrast to protein, in which the E-CLA cows consumed 120 g/day less protein than the controls with no concurrent reduction in protein yield in milk. However, in Odens et al (2007), no reduction in DMI and a significant improvement in EB were observed for cows fed CLA from 9 6 6 days pre-calving until 40 days post-calving.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…This is in contrast to protein, in which the E-CLA cows consumed 120 g/day less protein than the controls with no concurrent reduction in protein yield in milk. However, in Odens et al (2007), no reduction in DMI and a significant improvement in EB were observed for cows fed CLA from 9 6 6 days pre-calving until 40 days post-calving.…”
Section: Resultsmentioning
confidence: 85%
“…In several studies in which cows were fed a variety of CLA supplements in early or mid-lactation, no effect on DMI was observed (Piperova et al, 2004;Castañ eda-Gutié rrez et al, 2005;Castañ eda-Gutié rrez et al, 2007;Odens et al, 2007). However, a trend for lower intake was observed in cows fed calcium salts of CLA in early lactation (Selberg et al, 2004) or abomasally infused with CLA supplements (Baumgard et al, 2000).…”
Section: Resultsmentioning
confidence: 98%
“…The difference in response of the ACC-α transcripts in the mammary gland to CLA during the different stages of lactation might be explained by the magnitude of MFD or source of milk FA. Previous work in cows has demonstrated that higher doses of trans-10, cis-12 CLA are required to induce MFD during early lactation compared with mid and late lactation (CastanedaGutierrez et al, 2005;Odens et al, 2007). This may be due to transcript-specific regulation of ACC-α.…”
Section: Discussionmentioning
confidence: 97%
“…Hepatic triglyceride concentration was also unaffected during CLA-induced MFD (Bernal-Santos et al, 2003;Castañ edaGutiérrez et al, 2005). The mechanism of CLA is also independent of the stage of lactation as trans-10, cis-12 CLA reduces milk fat yield during all phases of the lactation cycle (Perfield et al, 2002;Bernal-Santos et al, 2003;Castañ edaGutiérrez et al, 2005), although a larger dose is required in early lactation (Moore et al, 2004;Odens et al, 2007).…”
Section: Mechanism Of Milk Fat Depressionmentioning
confidence: 99%
“…Under certain marketing systems and management schemes, it may be advantageous to reduce milk fat yield , and in some feeding and management systems the reduction in milk fat yield has allowed for a repartitioning of nutrients to support increased milk and milk protein yield (e.g. Bernal-Santos et al, 2003;Mackle et al, 2003;Lock et al, 2006b;Odens et al, 2007). Producers may also find it advantageous to induce MFD during periods of limited feedstuff availability such as inadequate rainfall in pasture-based systems or for a short period while breeding.…”
Section: Insights Gained From Milk Fat Depressionmentioning
confidence: 99%